2018
DOI: 10.1111/add.14244
|View full text |Cite
|
Sign up to set email alerts
|

Are changes in drinking related to changes in cannabis use among Swedish adolescents? A time–series analysis for the period 1989–2016

Abstract: From 1989 to 2016 there appears to be a positive association between alcohol and cannabis consumption among Swedish adolescents who use cannabis. This association seems to have become weaker over time, suggesting that alcohol and cannabis are neither substitutes nor complements among Swedish adolescents and that the recent decline in youth drinking is not associated with the increase in frequency of cannabis use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Some studies showed a negative association between marijuana and alcohol so that more use of one was associated with less use of the other (e.g., Alter et al, 2006;Chaloupka & Laixuthai, 1997;Crost & Guerrero, 2012;DiNardo & Lemieux, 2001), a pattern described as substitution. However, other analyses showed a positive association between marijuana and alcohol use, suggesting that use of one substance facilitates use of the other (e.g., Gripe et al, 2018;Gunn et al, 2018;Jones et al, 2018;Keith et al, 2015;Metrik et al, 2018;O'Hara et al, 2016;Pacula, 1998;Terry-McElrath et al, 2013;Williams et al, 2004;Yörük & Yörük, 2011), a pattern described as complementarity.…”
mentioning
confidence: 96%
“…Some studies showed a negative association between marijuana and alcohol so that more use of one was associated with less use of the other (e.g., Alter et al, 2006;Chaloupka & Laixuthai, 1997;Crost & Guerrero, 2012;DiNardo & Lemieux, 2001), a pattern described as substitution. However, other analyses showed a positive association between marijuana and alcohol use, suggesting that use of one substance facilitates use of the other (e.g., Gripe et al, 2018;Gunn et al, 2018;Jones et al, 2018;Keith et al, 2015;Metrik et al, 2018;O'Hara et al, 2016;Pacula, 1998;Terry-McElrath et al, 2013;Williams et al, 2004;Yörük & Yörük, 2011), a pattern described as complementarity.…”
mentioning
confidence: 96%
“…Omar et al extract words from article titles and propose a novel hybrid neural network model based on ARIMA model to forecast sales [ 26 ]. In Sweden, researchers use it to estimate the association between cannabis and alcohol use among teenagers [ 27 ]. Cortes et al also try to estimate the temporal patterns of dengue incidence in two Brazilian cities through ARIMA model [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The availability of cannabis has increased in Sweden during the past 10 years, although cannabis use has been quite stable during the last 20 years, with self-reported past-month use at about 2–4% among young people (16–29 years) [ 21 ]. There has, however, been a slight increase in frequent cannabis use among 16–19-year olds, where those reporting cannabis use have increased their use from an average of four times in 1989 to 13 times in 2016 [ 22 ]. Also, an increased cannabis potency in recent years might imply higher rates of harmful effects requiring healthcare.…”
Section: Discussionmentioning
confidence: 99%